2020
DOI: 10.3390/ma13030695
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Use of an Inorganic Bone Matrix in the Repair of Bone Defects in Rats Submitted to Experimental Alcoholism

Abstract: To assess the effects of chronic alcoholism on the repair of bone defects associated with xenograft. Forty male rats were distributed in: control group (CG, n = 20) and experimental group (EG, n = 20), which received 25% ethanol ad libitum after a period of adaptation. After 90 days of liquid diet, the rats were submitted to 5.0-mm bilateral craniotomy on the parietal bones, subdividing into groups: CCG (control group that received only water with liquid diet and the defect was filled with blood clot), BCG (co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Chitosan, calcium phosphate and collagen and their combination in composite materials meet the required properties (biocompatible, bioactive, biodegradable, and multifunctional) and can promote biostimulation for tissue regeneration 52 . In some situations of alteration by pathologies, the repair process and healing rate may be compromised even when these biomaterial are used 62 , 63 .…”
Section: Resultsmentioning
confidence: 99%
“…Chitosan, calcium phosphate and collagen and their combination in composite materials meet the required properties (biocompatible, bioactive, biodegradable, and multifunctional) and can promote biostimulation for tissue regeneration 52 . In some situations of alteration by pathologies, the repair process and healing rate may be compromised even when these biomaterial are used 62 , 63 .…”
Section: Resultsmentioning
confidence: 99%
“…This material is easy to manipulate for installation in the surgical bed. It is suggested that it is capable of providing new bone formation and growth, resulting in neoformed tissue with a firm clinical consistency and high cellular activity [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…Molecular studies involving alcoholics have identified elevated levels of sclerostin, a protein found in areas of bone resorption and an inhibitor of the wingless (Wnt) signaling pathway, with a consequent reduction in the expression of the β-catenin protein. The Wnt/β-catenin signaling pathway is responsible for osteoblastogenesis, which, when compromised, affects the differentiation, function, and half-life of osteoprogenitor cells and interferes with the balance between bone neoformation and resorption [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%